Synthetic Peptides to Target Stringent Response-Controlled Virulence in a Pseudomonas aeruginosa Murine Cutaneous Infection Model - Pletzer, Daniel; Wolfmeier, Heidi; Bains, Manjeet; Hancock, Robert E. W. (Frontiers in Microbiology, 2017)
Microorganisms continuously monitor their surroundings and adaptively respond to environmental cues. One way to cope with various stress-related situations is through the activation of the stringent stress response pathway. In Pseudomonas aeruginosa this pathway is controlled and coordinated by the activity of the RelA and SpoT enzymes that metabolize the small nucleotide secondary-messenger molecule (p)ppGpp. Intracellular ppGpp concentrations are crucial in mediating adaptive responses and virulence. Targeting this cellular stress response has recently been the focus of an alternative approach to fight antibiotic resistant bacteria. Here we examined the role of the stringent response in the virulence of P. aeruginosa PAO1 and the Liverpool epidemic strain LESB58. A ΔrelA/ΔspoT double mutant showed decreased cytotoxicity towards human epithelial cells, exhibited reduced hemolytic activity, and caused down-regulation of the expression of the alkaline protease aprA gene in stringent response mutants grown on blood agar plates. Promoter fusions of relA or spoT to a bioluminescence reporter gene revealed that both genes were expressed during the formation of cutaneous abscesses in mice. Intriguingly, virulence was attenuated in vivo by the ΔrelA/ΔspoT double mutant, but not the relA mutant nor the ΔrelA/ΔspoT complemented with either gene. Treatment of a cutaneous P. aeruginosa PAO1 infection with anti-biofilm peptides increased animal welfare, decreased dermonecrotic lesion sizes, and reduced bacterial numbers recovered from abscesses; resembling the phenotype of the ΔrelA/ΔspoT infection. It was previously demonstrated by our lab that ppGpp could be targeted by synthetic peptides; here we demonstrated that spoT promoter activity was suppressed during cutaneous abscess formation by treatment with peptides DJK-5 and 1018, and that a peptide-treated relA complemented stringent response double mutant strain exhibited reduced peptide susceptibility. Overall these data strongly indicated that synthetic peptides target the P. aeruginosa stringent response in vivo and thus offer a promising novel therapeutic approach.